Developing Module of Fractional Numbers using Contextual Teaching and Learning Approach - I Ketut Suastika; Dyah Tri Wahyuningtyas (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
The purpose of this study was to develop a learning module of fractional numbers using Contextual Teaching and Learning (CTL) approach. The stages of development adhered to the stages of development proposed by Plomp (2007). To assess the quality of the module, Neeven’s assessment of product quality (2007) was used. This assessment focused on three things: the validity, practicality, and effectiveness of the developed module. The validity of the module was determined by validators. Once the module was confirmed valid by the validators, the try-outs were administered to see the practicality and effectiveness. The practicality of the module was assessed from students’ activity and students’ responses on learning using the module. Meanwhile, the effectiveness of the module was assessed from the results of daily tests and final tests. The try-outs were conducted in class four times, and the percentage of students’ scores in each meeting was above 90%, which means that students did not experience difficulties and felt comfortable in shaping their learning experience, and students’ response was also positive. Meanwhile, the average daily test results of students for each meeting and the average final test results of all students were above 75. The results of these try-outs indicate that the developed module met the criteria of practicality and effectiveness.